2022
DOI: 10.1111/imj.15783
|View full text |Cite
|
Sign up to set email alerts
|

Understanding vaccine‐induced thrombotic thrombocytopenia (VITT)

Abstract: Vaccine-induced thrombotic thrombocytopenia (VITT) is a rare, but serious, syndrome characterised by thrombocytopenia, thrombosis, a markedly raised D-dimer and the presence of anti-platelet factor-4 (PF4) antibodies following COVID-19 adenovirus vector vaccination. VITT occurs at a rate of approximately 2 per 100 000 first-dose vaccinations and appears exceedingly rare following second doses. Our current understanding of VITT pathogenesis is based on the observations that patients with VITT have antibodies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…As for the mechanisms by which an adenoviral vector vaccine may cause ITT, it has been hypothesized that there may be a reaction between the cationic PF4 and the anionic free DNA contained in the recombinant vaccine ( 45 , 125 ). However, the underlying pathways by which COVID-19 vaccination may stimulate anti-PF4 antibody production need further examination.…”
Section: Discussionmentioning
confidence: 99%
“…As for the mechanisms by which an adenoviral vector vaccine may cause ITT, it has been hypothesized that there may be a reaction between the cationic PF4 and the anionic free DNA contained in the recombinant vaccine ( 45 , 125 ). However, the underlying pathways by which COVID-19 vaccination may stimulate anti-PF4 antibody production need further examination.…”
Section: Discussionmentioning
confidence: 99%
“…VITT is associated with elevated D-dimer and elevated anti-PF-4 antibodies. It is frequently complicated by thrombosis, including VST (Dix et al, 2022). About half of the patients with VITT experience a VST (Palaiodimou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…1,[36][37][38][39] Cumulatively, a few basic tenets subside in most criteria, including elevated D-dimer (> 4,000 μg/mL [fibrinogen equivalent units]), reduced fibrinogen (below the normal range), positive anti-PF4 antibodies by ELISA testing, thrombocytopenia (platelet count < 150 Â 10 9 /L), and an onset of symptoms after 4 days of adenovirus-based COVID vaccination. 40,41 Conversely, each criterion contains slight variations, mainly due to the timing of their release, influence of research based on newly reported cases, and whether they have been updated routinely. 3,32 Exemplarily was the exclusion of possible VITT cases outside of the 28-day, postvaccination period, which is now believed to be limiting to identification of prior potential cases.…”
Section: Diagnostic Criteria and Guidelinesmentioning
confidence: 99%
“…3,30,36,39 The use of ELISA assays for detecting anti-PF4 antibodies has thus far been largely accepted to confirm VITT. 40,41 In terms of reporting, however, this criterion is not yet extensively indispensable. For example, negative or obscure results for ELISA have been used in several cases.…”
Section: Diagnostic Criteria and Guidelinesmentioning
confidence: 99%